PERAN IBU RUMAH TANGGA DALAM MEWUJUDKAN PENDIDIKAN AKHLAK ANAK USIA DINI DI DESA SORO - Idhar, Idhar (FASHLUNA, 2023)
This study uses a descriptive qualitative study which aims to determine the role of housewives in realizing early childhood moral education in Soro Village, Bima Regency. Data collection through several ways, namely: observation, interviews and documentation. The results of this study found that the role of housewives in terms of early childhood moral education in Soro Village was to continue to add religious insight to housewives as early educators for children. Furthermore, in the process of educating, housewives in Soro Village make use of local wisdom values ​​as an educational strategy. The factors that influence moral education by housewives in Soro Village can be divided into two, namely the factor of the shaman and the inhibiting factor. For supporting factors; instinctively hereditary educational experience, big soul and high aspirations, feeling of loving and being loved. While the inhibiting factor is the family's economic problems.